Colossal Seebeck effect enhanced by quasi-ballistic phonons dragging massive electrons in FeSb2 - H. Takahashi (Nature Portfolio, 2016)
Thermoelectric performances depend on phonon and electron transport. Here, Takahashi et al. show that the large Seebeck coefficient observed in high-purity single-crystal FeSb2 is due to the phonon-drag effect and to the high effective mass of delectrons interacting with quasi-ballistic phonons.